Independent identification of meteor showers in EDMOND database. (1st December 2015) - Rudawska, R.; Matlovič, P.; Tóth, J.; Kornoš, L.
Abstract: Cooperation and data sharing among national networks and International Meteor Organization Video Meteor Database (IMO VMDB) resulted in European viDeo MeteOr Network Database (EDMOND). The current version of the database (EDMOND 5.0) contains 144 749 orbits collected from 2001 to 2014. This paper presents the results obtained by a proposed new independent method of meteor showers identification, which is applied to the current version of the database (EDMOND 5.0). In the first step of the survey we used the D SH criterion to find groups around each meteor within the similarity threshold. Mean parameters of the groups were calculated and compared using a new function D X based on geocentric parameters ( λ ⊙, α, δ, and V g ). Similar groups were merged into final clusters (representing meteor showers), and compared with the IAU Meteor Data Center list of meteor showers.